'Right to the city' and the New Urban Agenda: learning from the right to housing. Issue 4 (2nd October 2019) - Turok, Ivan; Scheba, Andreas
ABSTRACT: The 'right to the city' has influenced the New Urban Agenda and other global and national urban policies. In the process, the meaning has narrowed towards realizing human rights in cities. Pursuing the right to housing in South Africa has established an important duty on the state to ensure universal access to decent accommodation. This has enabled millions of the poorest households to obtain improved habitation, and others to gain protection against forced evictions. However, the single-minded focus on state delivery of mass housing has been unable to keep pace with the rising level of need. It has also neglected the economic requirements of households and is proving to be financially unsustainable. Consequently, the housing right has not lifted many people out of income poverty or created more inclusive cities. A rights-based approach needs to be complemented by collective action and strengthened capabilities to drive progress across a broader agenda than just housing, particularly at the local level where there are major obstacles to change. A purposeful approach to unlocking urban land and collective efforts to spur socioeconomic development are vital.